Progress or regression? Institutional evolutions of community‐based conservation in eastern and southern Africa. Issue 1 (15th October 2020) - Nelson, Fred; Muyamwa‐Mupeta, Patricia; Muyengwa, Shylock; Sulle, Emmanuel; Kaelo, Dickson
Abstract: Eastern and southern Africa has been a key laboratory for community‐based approaches to conservation for over three decades. During the 1990s, field‐level initiatives and national policy reforms across the region put it at the forefront of global experiments with community‐based conservation. Community‐based conservation, in theory and practice, is closely tied to institutional reforms that devolve rights over wildlife and natural resources to local communities. As such, these efforts have frequently encountered political‐economic and institutional barriers that limited their impact. This contributed to a rising sense of rollback and recentralization of community conservation approaches during the 2000s. Since then, community‐based conservation has expanded its scope considerably in some countries, notably Kenya and Namibia, primarily as a result of relatively supportive legal and policy provisions coupled with sustained government, civil society, and private sector support. At a wider scale, sufficient devolution of rights over wildlife and natural resources has been a chronic constraint, but community‐based initiatives have still managed to persist, adapt, and deliver some evidence of positive ecological and social impacts in Zambia, Tanzania, and Zimbabwe. Three key overarching trends across the region are (a) the significant growth and expansion of community‐based conservation where key institutional enabling conditions exist; (b) pervasive institutional limitations on community rights over wildlife and other valuable natural resources, which continue to constrain and undermine community‐based approaches; and (c) local entrepreneurship and resilience that continues to create new opportunities for community‐based approaches, even under adverse conditions.